Bibliometric Analysis of The Development of Forensic Audit Research Based on VOS-Viewer - Kurniawan, Sunny Agung; Mayuri, Ni Kadek Lila; Fitriana, F.; Santoso, Rachmat Agus (Golden Ratio of Finance Management, 2025)
This study aims to analyze the development and trends of research in forensic auditing through a bibliometric approach using VOSviewer software. Focusing on publications from 2012 to 2024, the study evaluates key themes, collaborations between researchers, and the relationship between methodology and geographic context. The method used is bibliometric analysis with a network visualization, overlay, and density approach, which maps keywords from related literature to identify thematic patterns and associations. The results of the study show three main thematic clusters. The first cluster highlights the relationship between forensic auditing and economic development, focusing on methodologies and contributions to economic growth. The second cluster emphasizes an empirical approach that uses primary and secondary data to evaluate the influence of certain variables in forensic audits. The third cluster focuses on the local context, particularly Indonesia, focusing on the application of technology in detecting and preventing economic crimes. The overlay visualization also reveals the evolution of research themes, from early conceptual issues such as "economy" and "methodology" to applicable topics such as "technology" and "crime." The study found that collaboration between researchers, institutions, and countries is crucial in expanding the scope of research and integrating technological innovations such as blockchain and data mining. These findings provide in-depth insights into trends, research gaps, and opportunities for future exploration, helping to strengthen the role of forensic audits in supporting financial transparency and accountability.